Coagulant recovery and reuse for drinking water treatment - Keeley, James; Jarvis, Peter; Smith, Andrea D.; Judd, Simon J. (Elsevier, 2015)
Coagulant recovery and reuse from waterworks sludge has the potential to significantly reduce waste disposal and chemicals usage for water treatment. Drinking water regulations demand purification of recovered coagulant before they can be safely reused, due to the risk of disinfection by-product precursors being recovered from waterworks sludge alongside coagulant metals. While several full-scale separation technologies have proven effective for coagulant purification, none have matched virgin coagulant treatment performance. This study examines the individual and successive separation performance of several novel and existing ferric coagulant recovery purification technologies to attain virgin coagulant purity levels. The new suggested approach of alkali extraction of dissolved organic compounds (DOC) from waterworks sludge prior to acidic solubilisation of ferric coagulants provided the same 14:1 selectivity ratio (874 mg/L Fe vs. 61 mg/L DOC) to the more established size separation using ultrafiltration (1285 mg/L Fe vs. 91 mg/L DOC). Cation exchange Donnan membranes were also examined: while highly selective (2555 mg/L Fe vs. 29 mg/L DOC, 88:1 selectivity), the low pH of the recovered ferric solution impaired subsequent treatment performance. The application of powdered activated carbon (PAC) to ultrafiltration or alkali pre-treated sludge, dosed at 80 mg/mg DOC, reduced recovered ferric DOC contamination to <1 mg/L but in practice, this option would incur significant costs. The treatment performance of the purified recovered coagulants was compared to that of virgin reagent with reference to key water quality parameters. Several PAC-polished recovered coagulants provided the same or improved DOC and turbidity removal as virgin coagulant, as well as demonstrating the potential to reduce disinfection byproducts and regulated metals to levels comparable to that attained from virgin material.
Keywords: Coagulant recovery and reuse; Dissolution; Ferric; Membrane separation; DOC